The Impact of Supply Chain Responsiveness on Sustainable Performance: A field Study of Manufacturing Companies in Malaysia - Istimaroh, (Research in Management of Technology and Business, 2022)
The objective of this study was to analyze the impact of supply chain responsiveness (SCR) on sustainable performance (SP) in Malaysian manufacturing firms. This study used a questionnaire to collect 231 replies. Statistical approaches such as descriptive statistics, correlation, and bootstrapping were used. Cronbach's Alpha and factor analysis were used to validate the data gathering appropriateness of instrument. The research findings validated the assumption that SCR has a positive effect on company SP. The current study results demonstrated that the primary hypothesis was accepted, as did the alternative, which asserts that the supply chain responsiveness variables OSR, LPR, and SNR impact SP. The findings also revealed that a greater level of OSR provides a higher level of SP for businesses, which is based on reduced pricing, high delivery dependability, high product innovation, and low time to market. It was also discovered that a greater level of SNR results in a higher level of SP for a firm, which is based on low pricing and high delivery reliability. This research has significant implications for practitioners. Based on the present levels of different particular impact SCR and its dimensions, this analysis gives appropriate suggestions on the opportunity for development. Furthermore, the study makes appropriate recommendations on the scope for development based on existing levels of many important SCR criteria that directly effect a SFP, in order to make the businesses more sustainable.